2014
DOI: 10.1186/s12989-014-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of rod-like carbon nanotubes causes unconventional allergic airway inflammation

Abstract: BackgroundCarbon nanotubes (CNT) represent a great promise for technological and industrial development but serious concerns on their health effects have also emerged. Rod-shaped CNT are, in fact, able to induce asbestos-like pathogenicity in mice including granuloma formation in abdominal cavity and sub-pleural fibrosis. Exposure to CNT, especially in the occupational context, happens mainly by inhalation. However, little is known about the possible effects of CNT on pulmonary allergic diseases, such as asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 63 publications
0
77
0
Order By: Relevance
“…MWCNT have been shown to stimulate allergy-like inflammation in mouse lung airways where expression of cytokines associated with Th2 functions, i.e., IL-4 and IL-13, was elevated (Rydman et al 2014). Allergen sensitization was found to induce the expression of IL-4 and IL-13, which appeared to suppress CNT-induced activation of inflammasomes (Shipkowski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MWCNT have been shown to stimulate allergy-like inflammation in mouse lung airways where expression of cytokines associated with Th2 functions, i.e., IL-4 and IL-13, was elevated (Rydman et al 2014). Allergen sensitization was found to induce the expression of IL-4 and IL-13, which appeared to suppress CNT-induced activation of inflammasomes (Shipkowski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lung exposure to rod-like (r) MWCNTs can lead to allergic airway inflammation and mucous cell metaplasia, while exposure to tangled (t) MWCNTs causes non-allergic lung inflammation with no mucous cell metaplasia [911]. Other properties of MWCNTs have been shown to play a role in their pulmonary toxicity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Other properties of MWCNTs have been shown to play a role in their pulmonary toxicity (i.e. length, surface charge, residual metals) yet only a few studies comparing MWCNTs with contrasting rigidity have been conducted [9, 12]. However, to our knowledge there are no studies that address genetic susceptibility to allergic or fibrogenic responses to MWCNTs with different rigidities.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials used in this study were previously characterized and reported in NANOATLAS (Vippola et al, 2009) as well as in our previous publications (Kinaret et al, 2017a;Rydman et al, 2015;Rydman et al, 2014;Palomäki et al, 2015). Providers and material characteristics are reported in Table 1.…”
Section: Nanomaterials and Suspensionsmentioning
confidence: 99%
“…We and others already showed that ENMs are able to exert toxic effects on the respiratory system, by using animal exposure models (Kinaret et al, 2017a;Rydman et al, 2015;Rydman et al, 2014). Apart from the pathological responses, ENMs MOA has been investigated in different tissues (Kinaret et al, 2017b;Fröhlich, 2017;Costa and Fadeel, 2016), by analyzing the molecular perturbations that these materials are able to induce on the normal transcriptional program of exposed cells and tissues.…”
Section: Introductionmentioning
confidence: 99%